Pengaruh Pemberian Ekstrak Kayu Siwak (Salvadore persica) 50% Dengan Frekuensi Yang Berbeda Terhadap Ketahanan Email Gigi Rattus norvegicus - Dewanti H, Gilang; Triawan, Andi (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2008)
Miswak (Salvadora Persica) have antibacterial substances which can reduce the amount of bacteria in mouth so the tooth become healthy and prevent incidence of holey tooth. Intention of this research is to analyze usage of 5 0% miswak extract with different frequencies (1 x one day, 3 days once and once a week) to acid resistance of Rattus norvegicus tooth enamel.Research subject use I5 Rattus norvegicus at the age of 20 old days. The treatment is given 50% miswak extract topically on the incisivus tooth of Rattus norvegicus lower jaw with different frequencies. Each group (consist of 5 Rattus norvegicus) divided based on the frequencies that giving. The frequencies are I x one day, once every 3 day and once every a week. Treatment conducted during 30 day. After Rattus norvegicus in the age of 51 days, incisivus tooth of Rattus norvegicus taken away from lower jaw. After that phosphoric acid gel 37% applied above entire/all surface of tooth. We roentgen the tooth with digitally periapical Roentgen and calculated the damage on the enamel with score.Research result indicate that the given of 5 0% miswak extract with frequency I x one day, once every 3 days and once a week have signiï¬cant difference (p=0,024) to acid resistance of Rattus norvegicus tooth enamel. Giving of 5 0% miswak extract with frequency I x is one day compared to with frequency once every 3 days also have difference which significant (p=0,042). While comparison between the giving of 50% miswak extract with frequency I x one day and once a week also have significant difference (p=0,020).Conclusions of research, the giving of miswak extract 5 0% with different frequency have different inï¬‚uence significantly to acid resistance of Rattus norvegicus tooth enamel. Miswak is a natural substance that can use for keep our mouth health.Â